The Last Man Who Knew Everything Thomas Young, the Anonymous Polymath Who Proved Newton Wrong, Explained How We See, Cured the Sick, and Deciphered the Rosetta Stone, Among Other Feats of Genius (Revised Edition) - Robinson, Andrew (Open Book Publishers, 2023)
No one has given the polymath Thomas Young (1773-1829) the all-round examination he so richly deserves-until now. Celebrated biographer Andrew Robinson portrays a man who solved mystery after mystery in the face of ridicule and rejection, and never sought fame. As a physicist, Young challenged the theories of Isaac Newton and proved that light is a wave. As a physician, he showed how the eye focuses and proposed the three-colour theory of vision, only confirmed a century and a half later. As an Egyptologist, he made crucial contributions to deciphering the Rosetta Stone. It is hard to grasp how much Young knew. This biography is the fascinating story of a driven yet modest hero who cared less about what others thought of him than for the joys of an unbridled pursuit of knowledge-with a new foreword by Martin Rees and a new postscript discussing polymathy in the two centuries since the time of Young. It returns this neglected genius to his proper position in the pantheon of great scientific thinkers.